2004
DOI: 10.1159/000071279
|View full text |Cite
|
Sign up to set email alerts
|

Hemoperfusion with Polymyxin B-Immobilized Fiber in Septic Patients with Methicillin-Resistant <i>Staphylococcus aureus</i>-Associated Glomerulonephritis

Abstract: Background/Aims: We investigated whether urinary podocytes are present in septic patients with methicillin-resistant Staphylococcus aureus (MRSA)-associated glomerulonephritis and whether polymyxin B-immobilized fiber (PMX-F) treatment affects proteinuria and urinary podocyte excretion in these patients. Methods: Twenty septic patients with MRSA-associated glomerulonephritis (mean age: 63.7 years) and 80 septic patients whose MRSA infection was not followed by glomerulonephritis (mean age: 60.5 years) were inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 24 publications
(39 reference statements)
2
16
0
Order By: Relevance
“…Since selection of antibiotics is at least partially influenced by treating center, it is reasonable to hypothesize variable effects of blood purification across centers, all other factors aside. Similarly, our results suggest that the main drivers for the beneficial effects of blood purification in this analysis come from studies of hemoperfusion with PMX-B, and were performed in a single country (29,30,31,33,34,36). Although the overall effects of blood purification without PMX-B were consistent with PMX-B studies ( p = 0.15; I 2 = 27%) the effect size is considerably smaller (RR 0.89 vs. 0.57) and fails to reach statistical significance.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Since selection of antibiotics is at least partially influenced by treating center, it is reasonable to hypothesize variable effects of blood purification across centers, all other factors aside. Similarly, our results suggest that the main drivers for the beneficial effects of blood purification in this analysis come from studies of hemoperfusion with PMX-B, and were performed in a single country (29,30,31,33,34,36). Although the overall effects of blood purification without PMX-B were consistent with PMX-B studies ( p = 0.15; I 2 = 27%) the effect size is considerably smaller (RR 0.89 vs. 0.57) and fails to reach statistical significance.…”
Section: Discussionsupporting
confidence: 52%
“…These trials were reported between 1999 and 2010. The Country of origin in six studies is Japan (29,30,31,33,34,36), all of which reported on hemoperfusion (Table 1, Table 2). The mean age of the study participants ranged from 33 to 75 years; 637 (77%) patients were admitted to the ICU (17,2429,3133,35); and the mean Acute Physiology and Chronic Health Evaluation (APACHE) II score was 24.2 (9,17,23,24,2736).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also a report that PMX-DHP improves the pathology of other types of sepsis besides the sepsis caused by Gram-negative bacteria [29]. However, in order to draw any conclusions about this, sepsis due to Gram-negative mixed infections would need to be completely excluded.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28][29][30][31][32][33][34][35] Table 1 summarizes the main studies on the use of Polymyxin B hemoperfusion. [26][27][28][29][30][31][32][33][34][35] Table 1 summarizes the main studies on the use of Polymyxin B hemoperfusion.…”
Section: Polymyxin B Hemoperfusion: Evidence Basementioning
confidence: 99%